O ensino de História e a Educação Indígena: desafios e possibilidades durante a Pandemia da Covid-19 na Escola Municipal Indígena Kokokangroti em Altamira-PA - SANTOS, Rafael Leal (2022)
History teaching, indigenous education and the challenges encountered during the COVID-19 pandemic are issues to be discussed in this research. In view of this, the objective of this work is to analyze the challenges of indigenous education, reflected on the educational practices in the teaching of History of the daily school life of the Kokokangroti Municipal Indigenous School during the Covid-19 pandemic. The research uses the participant method, linking itself to theory-practice and thought-action, through planning and pedagogical strategies that insert and give new meaning to the contents of indigenous history and culture. Where the teaching of History must be based on the culture of indigenous communities, where school education can be of great relevance in this process, that is, a process of dissemination and construction of knowledge among peoples. In view of this, a workshop was developed with the theme: a look at the community in history teaching. In which, the culture and resistance of the indigenous peoples of the middle Xingu must be seen and heard by the indigenous people themselves and by society.